Gougunao tea polysaccharides ameliorate high-fat diet-induced hyperlipidemia and modulate gut microbiota. Issue 2 (13th December 2022) - Deng, Qihuan; Wang, Wenjun; Zhang, Lieyuan; Chen, Lingli; Zhang, Qingfeng; Zhang, Ying; He, Sichen; Li, Jingen
Abstract : GTP40 improved the abnormal parameters related to lipid metabolism in the serum and liver, decreased oxidative and inflammatory stress, and played a regulatory role in shaping the gut microbiota of hyperlipidemia mice fed with a high-fat diet. Abstract : Many natural polysaccharides have been proven to have ameliorative effects on high-fat diet-induced hyperlipidemia with fewer side effects. However, similar data on Gougunao tea polysaccharides remain obscure. In this study, we aimed to investigate the role of Gougunao tea polysaccharides (GTP40) in the alleviation of hyperlipidemia and regulation of gut microbiota in C57BL/6J mice induced by a high-fat diet. The results indicated that GTP40 intervention inhibited the abnormal growth of body weight and the excessive accumulation of lipid droplets in the livers and ameliorated the biochemical parameters of serum/liver related to lipid metabolism in hyperlipidemia mice. The elevated levels of antioxidant enzyme and anti-inflammation cytokine in serum, as well as the up-regulating anti-inflammation gene in the liver, reflected that GTP40 might mitigate the oxidative and inflammatory stress induced by a high-fat diet. In addition, GTP40 could modulate the composition, abundance, and diversity of gut microbiota in hyperlipidemia mice. Besides, Spearman's correlation analysis implied that GTP40 intervention could enrich beneficial bacteria ( e.g., Akkermansia, Bacteroides, Roseburia, and Alistipes ), and decrease harmful bacteria ( e.g., Blautia, Faecalibaculum, Streptococcus, and norank_f_Desulfovibrionaceae ), which were correlated with the lipid metabolic parameters associated with hyperlipidemia. Moreover, it also indicated that there was a significant correlation between gut microbiota and SCFAs. Thus, GTP40 may be a novel strategy against fat accumulation, oxidative stress, and inflammation, as well as restoring the normal microbial balance of the gut in hyperlipidemia mice.